Increasing tourism through social entrepreneurship - the case of Croatia - Matošević Radić, Mijana; Jukić, Ivona, ekonomistica; Roje, Antonija (2020)
Social entrepreneurship is a relatively new topic of interest within the academic and the literature on it is limited. With the increase of interest in recent years from various interest groups, the concept of social enterprise has become more widespread. The purpose of this paper is to explore the link between social entrepreneurship and voluntourism, as one of the types of special interest tourism. Voluntourism, according to the concept of sustainable community development, relate all the stakeholders of such development. Moreover, social entrepreneurship could become an important vehicle for sustainable development of destinations. This paper proposes that niche tourism products and more specifically, voluntourism projects, under the prism of social entrepreneurship, can become the means towards Croatian product diversification and long-term environmental, social and economic sustainability. Quantitative research was conducted and the methodology entails a case study approach. Results indicate that there is a limited number of projects concerning social entrepreneurship in voluntourism in Croatia and also that discussed projects are not recognized. This study assessed the situation in Croatia and although it was comprehensive under conditions of limited data availability, it cannot speak to social entrepreneurship in voluntourism globally, but it can offer a foundation for future research in this area.
8th International OFEL Conference on Governance, Management and Entrepreneurship, Dubrovnik, 17.-18.4.2020.
Bibliografija: str. 35-38.
Abstract.
Keywords: Socijalno poduzetništvo -- Volonterski turizam -- Održivost; Hrvatska